The Plasma Membrane P-Type ATPase CtpA Is Required for Mycobacterium tuberculosis Virulence in Copper-Activated Macrophages in a Mouse Model of Progressive Tuberculosis - Marcela López-Ruíz; Jorge Barrios‐Payán; Milena Maya-Hoyos; Rogelio Hernández‐Pando; Marisol Ocampo; Carlos Y. Soto; Dulce Mata‐Espinosa (2025)
Background/Objective: Finding new targets to attenuate Mycobacterium tuberculosis (Mtb) is key in the development of new TB vaccines. In this context, plasma membrane P-type ATPases are relevant for mycobacterial homeostasis and virulence. In this work, we investigate the role of the copper-transporting P-type ATPase CtpA in Mtb virulence. Methods: The impact of CtpA deletion on Mtb's capacity to overcome redox stress and proliferate in mouse alveolar macrophages (MH-S) was evaluated, as well as its effect on Mtb immunogenicity. Moreover, the influence of CtpA on the pathogenicity of Mtb in a mouse (BALB/c) model of progressive TB was examined. Results: We found that MH-S cells infected with wild-type (MtbH37Rv) or the mutant strain (MtbH37RvΔctpA) showed no difference in Mtb bacterial load. However, the same macrophages under copper activation (50 µM CuSO4) showed impaired replication of the mutant strain. Furthermore, the mutant MtbΔctpA strain showed an inability to control reactive oxygen species (ROS) induced by PMA addition during MH-S infection. These results, together with the high expression of the Nox2 mRNA observed in MH-S cells infected with the Mtb∆ctpA strain at 3 and 6 days post-infection, suggest a potential role for CtpA in overcoming redox stress under infection conditions. In addition, MtbΔctpA-infected BALB/c mice survived longer with significantly lower lung bacterial loads and tissue damage in their lungs than MtbH37Rv-infected mice. Conclusions: This suggests that CtpA is involved in Mtb virulence and that it may be a target for attenuation.